“Whoa! we’re going deep in the trees!”: patterns of collaboration around an interactive information visualization exhibit - Davis, Pryce; Horn, Michael S.; Block, Florian; Phillips, Brenda; Evans, E. Margaret; Diamond, Judy; Shen, Chia (Springer, 2015)
In this paper we present a qualitative analysis of natural history museum visitor interaction around a multi-touch tabletop exhibit called DeepTree that we designed around concepts of evolution and common descent. DeepTree combines several large scientific datasets and an innovative visualization technique to display a phylogenetic tree of life consisting of over 70,000 species. After describing our design, we present a study involving pairs of children interacting with DeepTree in two natural history museums. Our analysis focuses on two questions. First, how do dyads negotiate their moment-to-moment exploration of the exhibit? Second, how do dyads develop and negotiate their understanding of evolutionary concepts? In order to address these questions we present an analytical framework that describes dyads’ exploration along two dimensions: coordination and target of action. This framework reveals four distinct patterns of interaction, which, we argue, are relevant for similar interactive designs. We conclude with a discussion of the role of design in helping visitors make sense of interactive experiences involving the visualization of large scientific datasets.